2017
DOI: 10.5222/jaren.2017.001
|View full text |Cite
|
Sign up to set email alerts
|

A study about knowledge level of pregnants that educated in pregnancy school

Abstract: ÖZ Amaç %53.36'dan %97.44'e, doğum bölümünde %51.98'den %97.7'ye, lohusalık bölümünde %44.56'dan %99.14'e, emzirme bölümünde %44.24'ten %100'e, bebek bakımı bölümünde %58.56' dan %99.72

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Although the pregnant women are invited to the classes regardless of their education level, the higher demand by pregnant women with higher education indicates that we should focus more on the less educated. The rate of women that were working was stated as 37.10% by Turgut et al [12] and in our study, the rate was 28.7%. The same study stated that women with their first pregnancy participated more (72.9%) and the results were similar in our study (73.3%).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Although the pregnant women are invited to the classes regardless of their education level, the higher demand by pregnant women with higher education indicates that we should focus more on the less educated. The rate of women that were working was stated as 37.10% by Turgut et al [12] and in our study, the rate was 28.7%. The same study stated that women with their first pregnancy participated more (72.9%) and the results were similar in our study (73.3%).…”
Section: Discussionsupporting
confidence: 54%
“…Most of them (94.7%) stated that they had a plan and they thought walking/moving would reduce the pain the most. In another study, breathing exercises were preferred the most by the participants [12]. Before the class, the participants were hesitant about the vaginal delivery but after the class, the rate of preference for vaginal delivery increased to 97.2%.…”
Section: Discussionmentioning
confidence: 93%
“…The results of the statistics on the NCF in Turkey and the studies on the pregnancy period in Turkey indicate that it should be explained to men and women who have decided to become a family that child development is multidimensional, that many variables affect the development, and that the development process of the unborn baby should begin while in the mother's womb. In a study on the knowledge levels of those who were educated at the pregnancy school and were also pregnant, it was found that the knowledge level of pregnant women increased significantly with the education provided, and those with their first pregnancy and university graduates participated in pregnant education at a higher rate (27).…”
Section: Good Healthmentioning
confidence: 99%
“…In this increase, the Ministry of Health's support of pregnant women in the direction of vaginal birth, raising awareness of the public through the media and other channels, and the training programs of health professionals working in the field of obstetrics, and their awareness of their duties, authorities, and responsibilities on this issue have been found to be effective (28). Today, prenatal classes aim to prepare expectant mothers and fathers for birth, to provide them with information about pregnancy, birth, postpartum period, and healthy growth of the baby, and to impart knowledge and skills so that they can adopt their new roles (27). The studies carried out in pregnant schools in Turkey mainly focused on reproductive health, preparation for childbirth, birth types, etc (29).…”
Section: Good Healthmentioning
confidence: 99%
“…Pregnant women receive routine antenatal care in family health centers or benefit from group training in pregnancy education programs in some hospitals. It has been reported that group training is useful for pregnant women, but there are problems involved, such as the limited number of pregnant women who have access to the service, the implementation of applications only in some hospitals, lack of a standard education model, and environmental limitations (13)(14)(15). It is feasible then that women can be provided with health information by means of new methods that are easily available and require no limits put on place or time.…”
Section: Introductionmentioning
confidence: 99%